Landscape effects on insect pests of Dracaena marginata and their associated natural enemies in Costa Rica - Linkimer Abarca, Mildred (CATIE, Turrialba (Costa Rica), 2014)
Tesis (Ph, D.) -- CATIE. Escuela de Posgrado, Turrialba (Costa Rica), 2012